Influence on Emotional Intelligence through Money Attitude against Consumptive Behavior of Student - Dyanti Mahrunnisya; Mintasih Indriayu; Dewi Kusuma Wardani (Journal of Education and Learning (EduLearn), 2018)
The research objective is to understand the influence on emotional intelligence through money attitude against consumptive behavior of student. The method used in this research was descriptive verification method with ex post facto and survey approach. The research held in Bandar Lampung City. Data collection technique were conducted by using questionnaires. Sampling technique in this study is Proportional Stratified Random Sampling, the number of samples as many as 165 students. The result showed 1) there is influence on emotional intelligence againts consumptive behavior of students in Bandar Lampung. The calculation obtained the coefficient of ρYX path was 0.289 which means the magnitude of influence on emotional intelligence against consumptive behavior as many as 0.289 or 28.9%. 2) The value of influence on emotional intelligence against consumptive behavior indirectly was obtained 5.15 %. In other words, emotional intelligence through money attitude has the role of the consumptive behavior of students.